2018
DOI: 10.1111/dom.13408
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting insulin doses in patients with type 1 diabetes who use insulin pump and continuous glucose monitoring: Variations among countries and physicians

Abstract: Physicians provide different insulin dose recommendations based on the same datasets. The automated advice of the Advisor Pro did not differ significantly from the advice given by the physicians in the direction or magnitude of the insulin dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
0
42
0
1
Order By: Relevance
“…However, the vast numbers of patients with T2D requiring intensive management presents a daunting challenge for a healthcare system already straining to meet increasing demand while at the same time struggling with shrinking visit times and reimbursements. Automated decision support (ADS) systems have the potential to assist clinicians and patients in optimizing insulin therapy; the selected articles highlight the progress and challenges in automating decision support in real world settings (16,17). For T2D management, which involves fewer variables than T1D management, simple algorithms and devices may be effective solutions for automated dose titration based on blood glucose data.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the vast numbers of patients with T2D requiring intensive management presents a daunting challenge for a healthcare system already straining to meet increasing demand while at the same time struggling with shrinking visit times and reimbursements. Automated decision support (ADS) systems have the potential to assist clinicians and patients in optimizing insulin therapy; the selected articles highlight the progress and challenges in automating decision support in real world settings (16,17). For T2D management, which involves fewer variables than T1D management, simple algorithms and devices may be effective solutions for automated dose titration based on blood glucose data.…”
Section: Commentmentioning
confidence: 99%
“…In contrast, the sheer volume of data and multitude of choices available to clinicians attempting to adjust therapy in patients with T1D using pumps and sensors makes development of ADS systems for this population a much more complex and challenging project. This interesting study by Nimri highlights the fact that there is little agreement or consistency among physicians regarding recommendations for insulin dosing changes for patients using pumps and sensors, lending credence to the old adage of medicine being as much an art as a science (16). The good news is that this at a very broad level, the particular ADS system under study, the Advisor Pro, seemed to agree with doctors as much as doctors agree with doctors.…”
Section: Commentmentioning
confidence: 99%
“…Some may be concerned that an ADS system running without physician oversight may provide unsafe recommendations to patients. The foundation for this concern has been addressed in a novel study by Nimri et al 17 This study evaluated the insulin dosing adjustments made by 26 physicians from 16 centers across Europe, Israel, and South America for pump settings based on CGM data. These adjustments were compared against the DreaMed Advisor Pro (DreaMed Diabetes Ltd., Petah Tikva, Israel).…”
Section: Rationale For Ads Technologymentioning
confidence: 99%
“…Earlier we discussed the Nimri study on the DreaMed advisor and its directional agreement with a diverse group of clinicians. 17 Herrero conducted an in silico validation of a basal insulin ADS tool for patients on CSII therapy. 26 This virtual study showed that use of the ADS tool could significantly improve time in target range and reduce hypoglycemia over a 4-month period.…”
Section: Studies On Ads Technologymentioning
confidence: 99%
“…Számukat jelenleg több mint egymillióra becsülik világszerte. 8 Az inzulinpumpák két főbb kategóriába sorolha- Mindkét esetben javasolt három-hatnaponta cserélni a kanült. Egy nemrégiben elvégzett átfogó vizsgálat eredménye nem mutatott ki szignifikáns különbséget az egyes gyártók és típusok közötti HbA 1c -értékek tekintetében.…”
Section: A Napjainkban Alkalmazott Inzulinpumpákunclassified